THE ROLE OF CREDIT IN REGIONAL ECONOMIC DEVELOPMENT - Eraliev A.A.; Abdugʻapparov Oybek (Ta'lim innovatsiyasi va integratsiyasi, 2026)
Annotation. This article examines the critical role and strategic impact of credit resources  on  fostering  regional  economic  development  and  narrowing  regional disparities.  The  author  analyzes  the  mechanisms  through  which  banking  and commercial credits stimulate local entrepreneurship, fund infrastructure projects, and attract  direct  investments  to  developing  territories.  By  evaluating  current  credit allocation patterns, the article identifies key structural challenges in regional financing, such as uneven distribution and access barriers for local enterprises.